2008
DOI: 10.1063/1.2965470
|View full text |Cite
|
Sign up to set email alerts
|

Local thermomechanical characterization of phase transitions using band excitation atomic force acoustic microscopy with heated probe

Abstract: An approach for thermomechanical characterization of phase transitions in polymeric materials (polyethyleneterephthalate) by band excitation acoustic force microscopy is developed. This methodology allows the independent measurement of resonance frequency, Q factor, and oscillation amplitude of a tip-surface contact as a function of tip temperature, from which the thermal evolution of tip-surface spring constant and mechanical dissipation can be extracted. We demonstrate a heating protocol which keeps the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 15 publications
0
50
0
Order By: Relevance
“…Impressive quantitative and numerous qualitative results have been reported with various modifications of the basic AFM system. [2][3][4][5][6][7][8][9] One such modification, contact resonance force microscopy (CR-FM) [10][11][12] has become an increasingly important technique for characterizing mechanical properties of materials at submicrometer scales. CR-FM methods use the resonant modes of the AFM cantilever in order to evaluate near-surface mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Impressive quantitative and numerous qualitative results have been reported with various modifications of the basic AFM system. [2][3][4][5][6][7][8][9] One such modification, contact resonance force microscopy (CR-FM) [10][11][12] has become an increasingly important technique for characterizing mechanical properties of materials at submicrometer scales. CR-FM methods use the resonant modes of the AFM cantilever in order to evaluate near-surface mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The Young’s modulus of the material can be calculated from the measured resonance frequency as Jesse et al have already showed 66. Different contact resonances can be used to calculate contact stiffness as a function of frequency: fitalicresitrue(1bik1k2true)f0BOUND where f res is the resonance frequency of the tip – surface contact, i is the order of the resonance, f 0BOUND is the resonance frequency of the tip in contact with infinitely stiff surface (this parameter depends only on the cantilever), k 1 is the spring constant of the cantilever, k 2 is the contact stiffness.…”
Section: Relationship Between Measured Parameters and Parameters Of Tmentioning
confidence: 99%
“…[3][4][5][6][7] Temperature calibration of heated AFM cantilevers is critically important for these and other applications. This article reports AFM cantilever temperature measurement and calibration under periodic heating.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5]8 By exciting the cantilever over a range of periodic heating frequencies, it is possible to measure substrate thermomechanical properties at the nanometerscale. 7 When the cantilever is in a magnetic field, periodic current flowing through the cantilever can induce Lorentz forces on the cantilever. The corresponding cantilever mechanical oscillation allows high resolution imaging.…”
Section: Introductionmentioning
confidence: 99%